2016
DOI: 10.1002/nau.22974
|View full text |Cite
|
Sign up to set email alerts
|

Effects of short‐term severe and long‐term mild STZ‐induced diabetes in urethral tissue of female rats

Abstract: Either long-term mild hyperglycemia or short-term severe hyperglycemia have detrimental impacts on muscle health. They are both involved in the failure to maintain healthy skeletal muscle that may contribute to the development of pelvic floor dysfunctions via different pathways. These results have important implications for monitoring and prevention strategies for improving the quality of life of women with diabetes mellitus and pelvic floor muscle dysfunction. Neurourol. Urodynam. 36:574-579, 2017. © 2016 Wil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 31 publications
3
25
0
Order By: Relevance
“…Female PFD is a common disorder that disables many women with diabetes during pregnancy but its etiology remains unclear [ [22][23][24],9]. Previous translational studies confirmed that a reduction in muscle content by diabetes may negatively affect the structural and functional integrity of the urethra [22][23][24]. The results are expressed as ratios of respective areas in mm 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Female PFD is a common disorder that disables many women with diabetes during pregnancy but its etiology remains unclear [ [22][23][24],9]. Previous translational studies confirmed that a reduction in muscle content by diabetes may negatively affect the structural and functional integrity of the urethra [22][23][24]. The results are expressed as ratios of respective areas in mm 2 .…”
Section: Discussionmentioning
confidence: 99%
“…The consequences of UI persist not only during pregnancy but up to 2 years post-partum and have a negative impact on the quality of life [14,15]. Previously, our research group conducted studies on the urethral tissue obtained from a pregnant Streptozotocin (STZ) rat model [16][17][18][19][20][21]. The hyperglycemia status in these rats is manifested by STZinduced necrosis of the pancreatic β-cells [22].…”
Section: Introductionmentioning
confidence: 99%
“…These characteristics differentiated the urethral striated muscles of short-term severe diabetic pregnant rats and long-term mild diabetic pregnant rats from virgin, pregnant and diabetic control groups [20]. The diabetic models were obtained by streptozotocin injection, and according to the dose and duration of the hyperglycemic stimulus, they are classified as short-term severe diabetes or long-term mild diabetes [25,26]. The increase in collagen and severe fibrosis may also affect the contractile properties of the urethra [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…The diabetic models were obtained by streptozotocin injection, and according to the dose and duration of the hyperglycemic stimulus, they are classified as short-term severe diabetes or long-term mild diabetes [25,26]. The increase in collagen and severe fibrosis may also affect the contractile properties of the urethra [26,27]. The ECM molecular analyses of urethral components showed no difference in type I and type III collagen expression levels in short-term severe diabetic pregnant rats.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation